Investigating the Influence of Water Injection on the Emissions of a Diesel Engine - Kettner, M.; Dechent, S.; Hofmann, M.; Huber, E.; Arruga, H.; R., Mamat; G., Najafi (Faculty Mechanical Engineering, UMP, 2016)
There are many methods to decrease the nitrogen oxide emissions of a diesel engine. One promising measure is water injection into the engine’sintake manifold. As emission limits become more and more stringent, the diesel engine NOx–particulate trade-off is a challenge for engine developers. To overcome this challenge, a single-point water injection system has been developed to investigate the influence of different amounts of injected water on the behaviour of a 4-cylinder diesel engine. The amount of injected water was varied from 0 to 100% water-to-fuel ratio in part-load operation (BMEP = 2, 3.5 and 5 bar). The influence on the intake air cooling effect, exhaust emissions, combustion and engine parameters was evaluated. The combustion temperature and the NOx emissions decreased drastically (63% NOx decrease for a BMEP of 5 bar and a waterto-fuel ratio of 100%). This benefit had the drawback of an increase of the particle matter emission at high water-to-fuel ratio. The combustion process and performance parameters regarding efficiency, torque and fuel consumption were marginally influenced by the water injection. This work has achieved a major reduction of NOx raw emissions of a diesel engine. Further research lines could include research on water injection at high load operation points in the engine map.